THE IMPACT OF CULTURE ON EDUCATION IN AFRICA: A RESOLUTION FROM THE ARISTOTELIAN PERSPECTIVE - Peter Bisong Bisong; Samuel Aloysius Ekanem (Jurnal Sosialisasi: Jurnal Hasil Pemikiran, Penelitian dan Pengembangan Keilmuan Sosiologi Pendidikan, 2020)
Africa over the years has been struggling to catch up with other continents in terms of educational advancement. Many theories have been postulated in attempts to fashion out a better course for education in the continent. In spite of these attempts, Africa still lags behind. This work through a critical analysis aims at showing the great part culture has played in the slow growth of education in the continent. The work argues that some aspects of African (Nigeria specifically) culture need to be done away with, if education must thrive well in the continent. The work therefore, advocates the use of ‘force training’ as Aristotle postulated in his Nicomachean Ethics to change these dysfunctional aspects of culture so that the functional one would blossom. It is when this is done that education will blossom in Nigeria as well as in other countries.